2004
DOI: 10.1007/s11176-005-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of dimethyl and di-tert-butyl 2-aryl-4-hydroxy-4-methyl-6-oxocyclohexane-1,3-dicarboxylates with difunctional nucleophiles

Abstract: The nature of the alkyl group in the ester moieties of dimethyl and di-tert-butyl 2-aryl-4-hydroxy-4-methyl-6-oxocyclohexane-1,3-dicarboxylates affects the direction of their reactions with difunctional nucleophiles. The dimethyl esters react with hydrazine hydrate to give the corresponding tetrahydroindazoles, while their tert-butyl analogs are converted under similar conditions into 6-hydrazones. Reactions of both dimethyl and di-tert-butyl 6-oxocyclohexane-1,3-dicarboxylates with hydroxylamine lead to forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The methods of further modification of the thus prepared cyclohexanones with mono-or polyfunctional nucleophiles are also well studied [20][21][22][23][24][25][26][27][28]. For instance, it was found that reactions of hydroxylamine [9], hydrazine [23,24], ethylenediamine [27], ethanolamine [8,26,27], ethylene glycol [4], substituted aromatic amines [20,21,25], tosylhydrazide [22] and benzidine [28] with diethyl-4-hydroxy-4-methyl-6-oxo-2-phenylcyclohexane-1,3-dicarboxylate give isoxazole, imidazole and 1,3-dioxolane rings, Schiff base condensation products, etc. Moreover, in some cases the cyclization processes depend on temperature, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of further modification of the thus prepared cyclohexanones with mono-or polyfunctional nucleophiles are also well studied [20][21][22][23][24][25][26][27][28]. For instance, it was found that reactions of hydroxylamine [9], hydrazine [23,24], ethylenediamine [27], ethanolamine [8,26,27], ethylene glycol [4], substituted aromatic amines [20,21,25], tosylhydrazide [22] and benzidine [28] with diethyl-4-hydroxy-4-methyl-6-oxo-2-phenylcyclohexane-1,3-dicarboxylate give isoxazole, imidazole and 1,3-dioxolane rings, Schiff base condensation products, etc. Moreover, in some cases the cyclization processes depend on temperature, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, dimethoxy- [4], diethoxy- [1 -3], and diisopropoxycarbonyl-substituted cyclohexanones [5] interact with hydrazine hydrate to form tetrahydroindazoles, and di-tert-butoxycarbonyl-substituted cycloketols form hydrazones [4].…”
mentioning
confidence: 99%
“…With the goal of elucidating the effect of alkyl radical in the alkoxycarbonyl group on the reactivity of 1,3-bis(alkoxycarbonyl)-substituted cyclohexanones (cyclic β-hydroxy ketones) [1][2][3][4][5][6] we synthesized 2-substituted diisopropyl 6-hydroxy-6-methyl-4-oxocyclohexane-1,3-dicarboxylates and studied their structure and reactions with mono-and difunctional nitrogen-containing nucleophiles. Compounds Ia-If were obtained by the known method, namely by diketone condensation of isopropyl acetoacetate with aromatic and heterocyclic aldehydes under conditions of base catalysis [1] (in the presence of piperidine; Scheme 1).…”
mentioning
confidence: 99%
“…Reactions of cyclic hydroxy ketones containing methoxy-or ethoxycarbonyl groups in positions 1 and 3 of the cyclohexane ring are known to react with hydrazine hydrate at the 1,3-dioxo fragment; the subsequent heterocyclization gives the corresponding tetrahydroindazoles [5,6]. Under similar conditions, bis(tert-butoxycarbonyl)-substituted analogs are converted into 6-hydrazones [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation